Mechanical properties of hepatocellular carcinoma cells - Zhang, Gang (World J Gastroenterol, 2002)
AIM: To study the viscoelastic properties of human hepatocytes and hepatocellular carcinoma (HCC) cells under cytoskeletal perturbation, and to further to study the viscoelastic properties and the adhesive properties of mouse hepatoma cells (HTC) in different cell cycle. METHODS: Micropipette aspiration technique was adopted to measure viscoelastic coefficients and adhesion force to collagen coated surface of the cells. Three kinds of cytoskeleton perturbing agents, colchicines (Col), cytochalasin D (CD) and vinblastine (VBL), were used to treat HCC cells and hepatocytes and the effects of these treatment on cell viscoelastic coefficients were investigated. The experimental results were analyzed with a three-element standard linear solid. Further, the viscoelastic properties of HTC cells and the adhesion force of different cycle HTC cells were also investigated. The synchronous G(1) and S phase cells were achieved through thymine-2-desoryriboside and colchicines sequential blockage method and thymine-2-desoryriboside blockage method respectively. RESULTS: The elastic coefficients, but not viscous coefficient of HCC cells (K(1) = 103.6 ± 12.6 N·m(-2), K(2) = 42.5 ± 10.4 N·m(-2), μ = 4.5 ± 1.9 Pa·s), were significantly higher than the corresponding value for hepatocytes (K(1) = 87.5 ± 12.1 N·m(-2), K(2) = 33.3 ± 10.3 N·m(-2), μ = 5.9 ± 3.0 Pa·s, P < 0.01). Upon treatment with CD, the viscoelastic coefficients of both hepatocytes and HCC cells decreased consistently, with magnitudes for the decrease in elastic coefficients of HCC cells (K(1): 68.7 N·m(-2) to 81.7 N·m(-2), 66.3% to 78.9%; K(2): 34.5 N·m(-2) to 37.1 N·m(-2), 81.2% to 87.3%, P < 0.001) larger than those for normal hepatocytes (K(1): 42.6 N·m(-2) to 49.8 N·m(-2), 48.7% to 56.9%; K(2): 17.2 N·m(-2) to 20.4 N·m(-2), 51.7% to 61.3%, P < 0.001). There was a little decrease in the viscous coefficient of HCC cells (2.0 to 3.4 Pa•s, 44.4 to 75.6%, P < 0.001) than that for hepatocytes (3.0 to 3.9 Pa•s, 50.8 to 66.1% P < 0.001). Upon treatment with Col and VBL, the elastic coefficients of hepatocytes generally increased or tended to increase while those of HCC cells decreased. HTC cells with 72.1% of G(1) phase and 98.9% of S phase were achieved and high K(1), K(2) value and low μ value were the general characteristics of HTC cells. G(1) phase cells had higher K(1) value and lower μ value than S phase cells had, and G(1) phase HTC cells had stronger adhesive forces [(275.9 ± 232.8) × 10(-10) N] than S phase cells [(161.2 ± 120.4) × 10(-10) N, P < 0.001). CONCLUSION: The difference in both the pattern and the magnitude of the effect of cytoskeletal perturbing agent on the viscoelastic properties between HCC cells and hepatocytes may reflect differences in the state of the cytoskeleton structure and function and in the sensitivity to perturbing agent treatment between these two types of cells. Change in the viscoelastic properties of cancer cells may affect significantly tumor cell invasion and metastasis as well as interactions between tumor cells and their micro-mechanical environments.